Quality of wheat lines solely expressing high-molecular-weight glutenin allelic variation of 1Dy 12. Issue 1 (2nd January 2023) - Dai, Shoufen; Zhai, Zhi; Yang, Wanjun; Liu, Qianyu; Jiang, Jiaqi; Li, Jian; Liu, Gang; Yan, Zehong
ABSTRACT: The high-molecular-weight glutenin subunits (HMW-GS) at Glu-D1 have a larger contribution to the processing property of wheat flours than those at the Glu-A1 and Glu-B1 loci and are always expressed in nature. Wheat lines missing one subunit at Glu-D1, either x or y, attract great interest for their potential quality value. Major quality parameters including SDS - sedimentation value, gluten-related indices, and other dough strength parameters such as development time, stability time, degree of softening, and farinograph quality numbers were tested in wheat lines solely expressing HMW-GS 1Dy12 from different backgrounds and compared with a weak gluten wheat control CN 16 to elucidate their quality potential. Wheat line solely expressing HMW-GS 1Dy12 derived from different genetic backgrounds showed similar but low SDS-sedimentation values (∼10 mL) and low wet gluten (∼20–25 g) and dry gluten contents (∼10 g). Additionally, wheat line solely expressing HMW-GS 1Dy 12 also showed a lower development time (<1 min), stability time (<1 min), and farinograph quality number (∼5–15), and a higher degree of softening (∼170–301), than the control CN 16. Wheat line solely expressing HMW-GS 1Dy 12 had a weak dough strength and may be used as a potential material for producing weak-gluten foods.